2019
DOI: 10.1016/bs.mie.2019.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the recombinant expression of active tyrosine kinase domains: Guidelines and pitfalls

Abstract: Protein tyrosine kinases (PTKs) are key signaling molecules and important drug targets. Although the efficient recombinant production of active PTKs is important for both pharmaceutical industry and academic research, most PTKs are still obtained from conventional, expensive and time-consuming insect-cell based expression. Host toxicity, kinase inactivity, insolubility and heterogeneity are among the reasons thought to preclude PTK expression in Escherichia coli. Herein we review these presumed roadblocks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…For tyrosine protein kinases in particular, problems such as low expression or the formation of inclusion bodies are frequently encountered. This might be due to the potential cytotoxicity of the tyrosine protein kinases or to misfolding [29,30]. Although large-scale expression of a human tyrosine kinase in E. coli is difficult, we have confirmed that all SFKs can be expressed at levels detectable by Western blotting (Figure 3A).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For tyrosine protein kinases in particular, problems such as low expression or the formation of inclusion bodies are frequently encountered. This might be due to the potential cytotoxicity of the tyrosine protein kinases or to misfolding [29,30]. Although large-scale expression of a human tyrosine kinase in E. coli is difficult, we have confirmed that all SFKs can be expressed at levels detectable by Western blotting (Figure 3A).…”
Section: Discussionsupporting
confidence: 55%
“…Non-specific phosphorylation of cellular proteins suggests that the functional heterologous kinase expression would alter the original functions of certain endogenous proteins. This may be one of the reasons for the difficulty of preparing human tyrosine kinases using E. coli hosts, as the toxicity of heterologous proteins in E. coli has been pointed out [30].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, with tyrosine protein kinases, such problems as low expression or the formation of inclusion bodies are frequently encountered. This might be due to potential cytotoxicity of the tyrosine protein kinases or to misfolding [7,8]. To overcome these problems, insect or mammalian cells are frequently used in preparing recombinant tyrosine kinases.…”
Section: Reportsmentioning
confidence: 99%
“…One of the factors that complicate functional studies of EGFR and the discovery of allosteric inhibitors is that full‐length EGFR family of receptors, that also contain HER2, HER3, and HER4 receptors, is challenging to obtain in a soluble form in vitro due to the difficulty of expressing transmembrane domains and the instability of the kinase domain (Diaz Galicia et al, 2019; Haacke et al, 2009). Truncated receptors are widely utilized to study the biochemical, structural, and functional aspects of this class of receptors (Aertgeerts et al, 2011; Jura et al, 2009; 2009; Kovacs, Das, et al, 2015; Kovacs, Zorn, et al, 2015; Littlefield et al, 2014; Zhang et al, 2006, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors that complicate functional studies of EGFR and the discovery of allosteric inhibitors is that full-length EGFR family of receptors, that also contain HER2, HER3, and HER4 receptors, is challenging to obtain in a soluble form in vitro due to the difficulty of expressing transmembrane domains and the instability of the kinase domain (Diaz Galicia et al, 2019;Haacke et al, 2009).…”
mentioning
confidence: 99%